Analysis of the Vulvar Skin Microbiota in Asymptomatic Women and Patients With Vulvar Lichen Sclerosus Based on 16S rRNA Sequencing - Liu, Xiaoxiao; Zhuo, Yingying; Zhou, Yunlu; Hu, Jun; Wen, Hongwu; Xiao, Changji (Frontiers in Cell and Developmental Biology, 2022)
Vulvar lichen sclerosus (VLS) is a chronic inflammatory skin disease that brings life-long and psychological distress to patients. It remains unclear whether this condition is related to changes in the skin microbial community. The aim of this study was to evaluate the compositional characteristics of the vulvar skin microbiota between VLS patients and asymptomatic postmenopausal women. We included 60 cases of postmenopausal patients in the outpatient vulvar clinic of Peking University First Hospital from August 2020 to October 2020. Thirty-one patients were diagnosed with VLS by vulvar skin biopsy (VLS group), while twenty-nine women were asymptomatic volunteers (control group). DNA was extracted from vulvar skin swabs of the VLS and control groups. The V3-V4 fragments of 16S rRNA were targeted for high-throughput sequencing and gene sequence analysis. The sequencing results were analysed by α diversity, β diversity, species composition, LEfSe analysis to compare the compositional differences of the vulvar skin microbiota between the two groups. Our study revealed that at the phylum level, patients with VLS had a lower relative abundance of Firmicutes (P<0.0001) and a higher relative abundance of Proteobacteria than the control group (P<0.0001). At the genus level, Lactobacillus spp. accounted for the largest proportion of the microflora in the asymptomatic controls, while the proportion of Prevotella spp. in the VLS group was the highest. In the VLS group, the relative abundance of Finegoldia spp., Ralstonia spp., Peptoniphilus spp., Anaerococcus spp., Campylobacter spp., Providencia spp. Kelbsiella spp., Ezakiella spp. and Escherichia-Shigella spp. was significantly increased compared with the control group. Although there was no significant difference in the α diversity of the vulvar skin microbiota, the β diversity differed significantly between the two groups.